Comparative Evaluation of Nutritional Quality and In Vitro Protein Digestibility in Selected Vegetable Soybean Genotypes at R6 and R8 Maturity - Soujanya, Kanneboina; Supraja, T.; Kuna, Aparna; Nair, Ramakrishnan M.; Triveni, S.; Yogendra, Kalenahalli (MDPI, 2025)
The nutritional and quality characteristics of improved vegetable soybean genotypes were evaluated and compared with those of a grain-type soybean at the R6 (green maturity) and R8 (physiological maturity) stages. Significant variation (p < 0.05) was observed among genotypes for all measured traits. The overall quality parameters increased from the R6 (green maturity) stage to the R8 (physiological maturity) stage. Among the R6-stage genotypes, AVSB2001 recorded the highest contents of protein (15.30 ± 0.57 g/100 g), ash (2.31 ± 0.06 g/100 g), fat (8.05 ± 0.17 g/100 g), and calcium (140.78 ± 0.97 mg/100 g). The genotype Karune exhibited significantly higher levels of total sugars, non-reducing sugars, iron, and magnesium than the other entries. At the R8 stage, Swarna Vasundhara showed the highest protein content (39.23%), while AGS 447 recorded the highest values for fat, total sugars, in vitro protein digestibility, iron, copper, magnesium, and manganese. Notably, in vitro protein digestibility was lower across all genotypes at the R8 stage compared to the R6 stage. These findings suggest that selected vegetable soybean genotypes possess substantial nutritional value and can contribute meaningfully to meeting the recommended dietary allowance (RDA) across different age and occupational groups, underscoring this research’s potential public health impact. Based on stage-specific quality profiles, R6-stage genotypes may be better suited for fresh vegetables, whereas R8-stage genotypes can be utilized similarly to grain-type soybean for processing into products such as dhal, oil, flour, and other value-added foods.